2002
DOI: 10.1139/b01-142
|View full text |Cite
|
Sign up to set email alerts
|

The effects of salt, manganese, and density on life history traits in Hesperis matronalis L. from oldfield and roadside populations

Abstract: Plant communities in the verges of major roadways (roadsides) are similar to those of abandoned farm fields undergoing succession (oldfields). However, roadsides are subject to distinctive stresses. Here, we look at local adaptation in Hesperis matronalis L. to salinity and manganese (Mn). Plants collected from three roadside and three oldfield populations were grown in a greenhouse under controlled, high-salinity, and high-Mn conditions, and several life history traits were measured. In addition, we imposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Lowry et al (2008) showed an influence of salt spray in local adaptation among coastal and inland populations of Mimulus guttatus . However, adaptation to salinity differences may not be strong if values are below the limits of salinity stress (Rothfels et al, 2002; van Zandt et al, 2003; Pathikonda et al, 2010). Climate is often cited as the main driver of local adaptation on large geographic scales (Joshi et al, 2001; Etterson, 2004; Macel et al, 2007; Leinonen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Lowry et al (2008) showed an influence of salt spray in local adaptation among coastal and inland populations of Mimulus guttatus . However, adaptation to salinity differences may not be strong if values are below the limits of salinity stress (Rothfels et al, 2002; van Zandt et al, 2003; Pathikonda et al, 2010). Climate is often cited as the main driver of local adaptation on large geographic scales (Joshi et al, 2001; Etterson, 2004; Macel et al, 2007; Leinonen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This species is present in most of the United States, excluding the most southern states (USDA-NRCS 2011). Damesrocket is found in habitats similar to garlic mustard and is most common in open woods, mesic bottomlands, and roadsides (Francis et al 2009;Mitchell and Ankeny 2001;Rothfels et al 2002). Garlic mustard and damesrocket are often found growing together in the same habitats (Francis et al 2009;Murphy et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Hesperis matronalis populations are polymorphic for floral colour, with purple or white morphs, although some populations contain a pink intermediate (Dvořák 1982; Mitchell & Ankeny 2001; Rothfels et al 2002). Purple morphs have high levels of anthocyanins in their petals, whereas white morphs have little or no floral pigment.…”
Section: Methodsmentioning
confidence: 99%